Analysis of Strength, Endurance, Flexibility Towards Speed of 100 Meter Bifins Diving Athletes of Shima Sport Club - Pradana, Saka Putra Adi; Sungkowo, Sungkowo; Ramadhan, Indra; Permono, Purwono Sidiq (Jurnal Abdimas, 2025)
This study aims to analyze the relationship between back strength (Back), leg strength (Leg), body pulling ability (Pull Up), cardiovascular endurance (12-minute Run), and flexibility (Sit & Reach) to Bifins performance in 10 diving athletes. Data were analyzed using the Shapiro-Wilk normality test and Pearson correlation. The results of the normality test showed that all variables were normally distributed (p > 0.05). Correlation analysis revealed a positive and significant relationship between the variables Leg (r = 0.653, p = 0.040), Pull Up (r = 0.905, p < 0.001), 12-minute Run (r = 0.638, p = 0.047), and Sit & Reach (r = 0.873, p = 0.001) with Bifins performance. While back strength ( Back ) did not show a significant correlation with Bifins (r = -0.195, p = 0.588). These results indicate that leg strength, pulling ability, endurance, and flexibility are important factors that affect the performance of diving athletes. This study provides a basis for developing training programs that focus on these aspects to improve the performance of diving athletes.